2022
DOI: 10.1021/acs.analchem.2c01131
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Drawing Board: A Unifying First-Principle Model for Correlating Sample UV–Vis Absorption and Fluorescence Emission

Abstract: The popular textbook and literature model I(λ x ,λ m ) = λ λ − − K( , )(1 10 ) A x m x or its variants for correlating the sample absorption and fluorescence often fails even for the simplest samples where the fluorophore is the only light absorber. Reported is a first-principle model I(λ x ,λ m ) = λ λ − + K A ( , ) 10 A d A d x m x,f ( ) x,s x m,s m for correlating the sample fluorescence measured with a conventional spectrofluorometer and its UV−vis absorbance quantified with a conventional UV−vis spectroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…One example is the inner filter effect (IFE) imposed by the sample light absorption. The absorption IFE introduces nonlinearity to light scattering, Raman scattering, surface-enhanced Raman scattering, and fluorescence emission intensities as a function of the analyte concentration and causes spectral distortion. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example is the inner filter effect (IFE) imposed by the sample light absorption. The absorption IFE introduces nonlinearity to light scattering, Raman scattering, surface-enhanced Raman scattering, and fluorescence emission intensities as a function of the analyte concentration and causes spectral distortion. …”
Section: Introductionmentioning
confidence: 99%
“…There is extensive literature on the effects of light absorption on optical spectroscopic measurements, including the mathematical models for correcting the absorption IFE on the sample scattering and fluorescence intensities. However, the literature studying the impact of light scattering on spectroscopic measurements is sporadic. For example, questions like the general applicability of Beer’s law for experimental scattering extinction have, to our knowledge, not been critically examined.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can lead to questionable conclusions because the fluorophore emission intensity is related to both its fluorescence QY and its light absorption in a rather complex manner, as shown in a recently developed firstprinciple model. 39 Third, the existing literature has been predominantly focused on the temperature effects at the fluorophore Stokes-shifted fluorescence (SSF). A few recent works have been devoted to the temperature effects on anti-Stokes-shifted fluorescence (ASSF).…”
Section: ■ Introductionmentioning
confidence: 99%
“…51 The use of the TPL method for studying the temperature effects on the optical properties of PL materials is inspired by our recent work performed with anthracene (ANT). 39 This earlier work showed that the temperature effect on ANT fluorescence depends on the employed excitation and emission wavelengths. However, the general applicability of the conclusion is unknown because ANT is the only fluorophore used, and only four excitation wavelengths were employed for fluorescence excitation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation